Protective effect of butylated hydroxytoluene on sperm function in human spermatozoa cryopreserved by vitrification technique. (24th February 2014) - Merino, O.; Aguagüiña, W. E.; Esponda, P.; Risopatrón, J.; Isachenko, E.; Isachenko, V.; Sánchez, R.
Summary Butylhydroxytoluene (BHT), a synthetic analogue of vitamin E, shows antioxidant and antiviral properties and has been successfully used for mammalian sperm cryopreservation. In this study, BHT was included in a vitrification solution to determine its cryoprotective effect on human spermatozoa. Spermatozoa were selected by swim‐up and vitrified in close sealed straw using either a combination of human tubal fluid (HTF), sucrose and BHT 1 mm (VMBHT), or only HTF and sucrose (VM). The optimal concentration of BHT was determined by the observation of preserved progressive sperm motility (PSM) after warming and detection of plasma membrane (PMI), membrane mitochondrial potential (ΔΨm) and DNA integrity. The presence of reactive oxygen species (ROS) was also detected. The PSM was significantly higher in the VMBHT group (80.86 ± 5.41%) compared with the VM group (68.9 ± 3.67%) (P < 0.05). Butylhydroxytoluene significantly preserved DNA integrity (4.0 ± 0.1% versus 6.1 ± 1.6%; P < 0.05) and reduced ROS production (5.5 ± 2.2 versus 8.6 ± 1.8%; P < 0.05). Plasma membrane and ΔΨm showed no statistical differences. One millimolar BHT effectively maintained cell function and due to its antioxidant and antiviral properties could be used in semen cryopreservation of patients with viral infections transmitted by seminal plasma.